Knowledge, attitude and practice towards blood and body fluid exposure among students in heal th Campus, Universiti Sains Malaysia - Hosni, Anis Hanini (Universiti Sains Malaysia, 2016)
The burden of exposure to blood-borne pathogens (such as HIV, hepatitis B and c viruses) is highly considerable for healthcare workers. Healthcare workers including students and trainees, whose activities involve contact with blood or body fluids frcrn patients. The aim of this study is to determine the prevalence of awareness towards blood and body fluid exposure among students in Health Campus, Universiti Sains IV1alaysia. A self- administered questionnaire were completed by 158 students frcrn February to April 2016 to seek their knowledge, attitude and practice towards blood and body fluid exposure. The sample study consisted of 67 students from School of lv1edical Science (42.4%), 56 students from School of Dental Science (35.4%) and 35 students from Nursing Programme (22.2%). Overall, dental students displayed the highest percentage (67.9%) who scored highest point for each part. Total respondents' knowledge of blood-borne disease/infection was also classified under good level. Although percentage of the students had knowledge of "hand washing after accidental contact with blood and body fluid may help to reduce the infection risk'' is more than 95%, yet the number of student that were practicing was lower and significant (p=0.019). In conclusion, medical, dental and nursing students of USM Health Campus have satisfactory knowledge, attitude and practice towards blood and body fluid exposure. However, certain improvement and recommendation can be implemented by university management in terms of curriculum to enhance better performance in future.